Female and older workers in part-time employment in Singapore - Goh, Yee Leng (2015)
In 1992, part-time employment in Singapore constituted only 2.2% of the total workforce (Singapore Labour Force Survey, 1992). This is considerably low as compared to other countries like Norway and Britain that have 25.6% and 24.7% of part-time employment in the workforce, respectively (The Straits Times, 1989). Besides lagging behind other countries in tapping part-timers, Singapore also under-utilises them to resolve the labour shortage problem. Female and older workers are the two largest groups of part-timers in Singapore. This study attempts to highlight the problems encountered by female and older workers in the labour force (e.. work family conflict). Part-time employment is suggested as an alternative work arrangement to help female and older workers reduce their problems. Furthermore, it is suggested that the government and unions can promote the use of part-timers in companies through the provision of incentives, training and development, child-care facilities, etc.